VIOLENCE AGAINST WOMEN; CAUSES AND REMEDIES - Aadil Ahmad Mir; Altaf Hussain Ganie (International Engineering Journal For Research & Development, 2022)
Many women in our society are subjected to abusive treatment by their intimate relationships while suffering in silence. Domestic abuse can result in a woman's death in some situations. This must not continue since women are critical to the growth and development of any nation and the planet at large. They are guardians of society's social, cultural, and fundamental values, and they are frequently the most effective agents of change.Without their understanding, cooperation, and active participation, full community development is impossible. Women, in light of all of this, deserve better treatment, yet this is rarely the case. Wife battering has a negative impact on battered women's physical and mental health, as well as their children's. The meaning of violence against women, varieties of intimate partner violence, and the repercussions of different types of violence on battered women and their children are all discussed in this study. Domestic violence against women is also discussed in this study, as well as the causes and management of the problem. Finally, proposals were made to eliminate this threat from society.